Empowering Communities: Contextualizing Living Hadith on Mosque Building for Modern Islamic Development - Ahmad Siddiq Setiawan; Amrullah Harun; Nasaruddin (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2025)
This article examines the contextualization of hadith interpretation in relation to the construction of mosques at the Darul Muttaqin Mosque in Makassar City. The research stems from mosque management practices believed to be rooted in pro-phetic traditions (hadith). This article aims to understand the mosque administrators' comprehension of the hadith on mosque construction that forms the foundation of their understanding. This is a field study employing a descriptive-qualitative method, grounded in a phenomenological approach. Primary data was obtained through interviews, and secondary data was sourced from relevant literature. The research findings and discussion indicate that the administrators of the Darul Muttaqin Mosque understand the hadith on building mosques as encompassing not only the construction of a mosque from scratch, but also the management of the mosque through infrastructure improvements and community empowerment within the mosque, which are also considered essential components of building a mosque. The research demonstrates that the hadith on mosque construction can be contextualized beyond literal building to include ongoing management, infrastructure development, and community empowerment, providing a practical framework for modern mosque administration rooted in prophetic traditions. Additionally, it highlights the "living hadith" approach in a real-world setting, offering a model that integrates theological motivation with socio-economic initiatives to enhance mosques as multifaceted community hubs.